SEASONAL COURSE OF SURFACE OZONE AND ANTHROPOGENIC AIR POLLUTION IN THE CITIES OF BELARUS IN 2024 - Akimov, Aleksandr; Liudchik, Alexander; Paulenka, Pavel; Melnik, Elena; Sidorkina, Katsiaryna; Yarotau, Aliaksei (Journal of the Belarusian State University. Ecology, 2026)
Based on observation data from the National Environmental Monitoring System, the levels of anthropogenic air pollution and ground-level ozone in regional cities of Belarus and the Berezina Biosphere Reserve are analyzed, and the features of the seasonal and diurnal course in concentrations in 2023 and 2024, monitored by automatic observation cites of Belhydromet, are studied. The monthly average, long-term average values and average annual concentration values in 2023 and 2024 for each observation point are calculated and compared. It is shown that the observation results differ not only for different cities, but also for different observation points within the same city. The seasonal variation of concentrations also differs in the years under consideration, demonstrating deviations from long-term average monthly concentrations. Cities (measurement points) with the highest and lowest content of O3 and other measurable impurities in 2024 are determined. The dynamics of the content of O3 and other measurable impurities in 2023–2024 for each city (measurement point) is studied. A comparative analysis of the content of CO, NO2, NO and VOCs is carried out for several measurement points in Minsk and Mogilev in 2024. Cities (measurement points) in Belarus with the highest and lowest concentrations of pollutants are identified. The ratio of benzene, toluene, and xylene concentrations to the total VOC concentration is analyzed for each measurement point. A significant increase in the average annual total concentration of VOCs and each of the components for Gomel 14 in 2024 is noted. The degree of variability (consistency) in pollutant concentrations throughout the year is studied for each measurement point. Deviations from the previously described diurnal course of ground-level ozone concentrations and other measured air pollutants in cities (measurement points) of Belarus are determined.